PENGARUH KOMPENTENSI GURU DAN MOTIVASI GURU TERHADAP MUTU PENDIDIKAN DI SMK TEKSTIL PANDAAN - Lusiana Devi; Hadi Sunaryo; M. Khoirul ABS (E-JRM : Elektronik Jurnal Riset Manajemen, 2019)
ABSTRACT                                     This research was conducted with the aim of analyzing how the influence of Human Resource competence and Teacher Motivation on the Quality of Education in the Textile Vocational School of Pandaan. The sample in this study were as many as 79 respondents of students of SMK Textile Pandaan. The analysis method used in this study is Multiple Linear Regression with the SPSS Version 22 For Windows application. Based on the results of the hypothesis test, it was found that the simultaneous test results showed that the calculated F value was 2439.594 with F significance of 0,000 (0,000 <0,05) so that it could be concluded that teacher competency and teacher motivation had an effect on the quality of education at SMK Textile Pandaan. variable test Teacher Competence and motivation show that partially Variables Teacher Competence and motivation have a positive effect on Education Quality.Keywords: Teacher Competence, Teacher Motivation, Education Quality